The kombucha from Rhizophora mucronata Lam. herbal tea: Characteristics and the potential as an antidiabetic beverage - Hardoko; Evi K. Harisman; Yunita E. Puspitasari (Journal of Pharmacy & Pharmacognosy Research, 2020)
Context: Kombucha from tea is reported to be beneficial for health. Moreover, it can be used as a hepatoprotective, antiproliferative, antimicrobial, antidiabetic, and antilipidemic agent and is capable of healing stomach ulcers. But kombucha from other herbal has not been studied, including kombucha from the mangrove (Rhizophora mucronata) fruit.